2012
DOI: 10.1177/1074248412468945
|View full text |Cite
|
Sign up to set email alerts
|

Glimepiride Treatment Facilitates Ischemic Preconditioning in the Diabetic Heart

Abstract: Aims: The diabetic heart is resistant to the myocardial infarct-limiting effects of ischemic preconditioning (IPC). This may be in part due to the downregulation of the phosphatidylinositol 3 0 -kinase-Akt pathway, an essential component of IPC protection. We hypothesized that treating the diabetic heart with the sulfonylurea, glimepiride, which has been reported to activate Akt, may lower the threshold required to protect the diabetic heart by IPC. Methods: Goto-Kakizaki rats (a type II lean model of diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 63 publications
2
16
0
Order By: Relevance
“…Interestingly, in a recent study of diabetic rat hearts resistant to IPC, glimepiride was able to elicit cardioprotection. [44] Studies of sulfonylurea effects on IPC in humans are equally difficult to interpret, but also generally demonstrate that glyburide abolishes while glimepiride preserves IPC; very little is known of glipzide’s effects (Table 2). Despite this body of work, it is unknown whether long-term sulfonylurea exposure in persons with T2DM has clinically meaningful effects on IPC or related endpoints.…”
Section: Proarrhythmic and Antiarrhythmic Actions Of Sulfonylureasmentioning
confidence: 99%
“…Interestingly, in a recent study of diabetic rat hearts resistant to IPC, glimepiride was able to elicit cardioprotection. [44] Studies of sulfonylurea effects on IPC in humans are equally difficult to interpret, but also generally demonstrate that glyburide abolishes while glimepiride preserves IPC; very little is known of glipzide’s effects (Table 2). Despite this body of work, it is unknown whether long-term sulfonylurea exposure in persons with T2DM has clinically meaningful effects on IPC or related endpoints.…”
Section: Proarrhythmic and Antiarrhythmic Actions Of Sulfonylureasmentioning
confidence: 99%
“…Gu et al (2008) found that simvastatin treatment was able to restore cardioprotection elicited by ischemic preconditioning in the presence of hyperglycemia, and this effect was associated with the generation of NO. Pretreatment of diabetic Goto-Kakizaki rats with the antidiabetic sulfonylurea glimepiride (which did not reduce infarct size itself) was demonstrated to restore the sensitivity of the myocardium to ischemic preconditioning, such that one cycle instead of three cycles of ischemic preconditioning was sufficient to limit infarct size (Hausenloy et al, 2013c). However, this effect of glimepiride in lowering the threshold for ischemic preconditioning appeared to be independent of serum glucose levels, because the latter remained unchanged with glimepiride treatment (Hausenloy et al, 2013c).…”
Section: Diabetesmentioning
confidence: 99%
“…Pretreatment of diabetic Goto-Kakizaki rats with the antidiabetic sulfonylurea glimepiride (which did not reduce infarct size itself) was demonstrated to restore the sensitivity of the myocardium to ischemic preconditioning, such that one cycle instead of three cycles of ischemic preconditioning was sufficient to limit infarct size (Hausenloy et al, 2013c). However, this effect of glimepiride in lowering the threshold for ischemic preconditioning appeared to be independent of serum glucose levels, because the latter remained unchanged with glimepiride treatment (Hausenloy et al, 2013c). Finally, chronic insulin treatment increases cardiac adiponectin and restores cardioprotective AMPK signaling .…”
Section: Diabetesmentioning
confidence: 99%
“…Sulfonylureas have been shown to inhibit protection of ischemic preand postconditioning by blocking the ATP-sensitive K + channel in cardiomyocytes, but the effects on pre-and postconditioning are actually not uniform across sulfonylureas [125]. Recently, glimepiride treatment has shown to facilitate the cardioprotective effect elicited by ischemic preconditioning in the diabetic heart [126], while ACE inhibition and food restriction have shown to restore delayed preconditioning in diabetic mice [118].…”
Section: Reactivation Of Endogenous Cardioprotectionmentioning
confidence: 99%